The Utility (or Not) of Self‐Report Instruments in Family Assessment for Child and Adolescent Conversion Disorders?. Issue 4 (December 2016) - Kozlowska, Kasia; Cruz, Catherine; Davies, Fiona; Brown, Kerri J.; Palmer, Donna M.; McLean, Loyola; Scher, Stephen; Williams, Leanne M.
Abstract : Children and adolescents with conversion disorders and their families are challenging to understand and challenging to treat. This study examined whether self‐report instruments are a useful adjunct to family and individual assessment. A total of 57 children and adolescents diagnosed with conversion disorders and 57 sex‐ aged‐matched controls, along with their parents, completed the Strength and Difficulties Questionnaire, Child Behaviour Checklist, Depression Anxiety and Stress Scales, Somatic and Psychological Health Report (SPHERE), Brief Risk‐Resilience Index for Screening, and the NEO–Five‐Factor Inventory. The conversion disorder and control groups were compared on each questionnaire, and classified participants as 'cases' or not according to established clinical thresholds for each questionnaire. A discriminant analysis was used to examine which components of the SDQ, CBCL, DASS, SPHERE, BRISC, and NEO‐FFI emerged as most useful in identifying the clinical characteristics of children with conversion disorders. The role of attachment strategy with regards to the utility of self‐report measures was also examined. The SPHERE was the only self‐report that our patient cohort were able to utilise to communicate their somatic and emotional discomfort and distress. Our results suggest that children and adolescents presenting with functional somatic symptoms represent a distinctive clinical population for which the 'psychological' focus of most currently available questionnaires is not useful for identifying the presence of somatic illness or of comorbid anxiety and depression, and that these measures – with the exception of the SPHERE – are not a useful adjunct to a family‐based assessment. Therapeutic conversations that utilise language that asks about the state of the body – the body's response to stress, illness, pain, and injury – facilitate engagement and serve as the cornerstone of treatment.